Desenvolvimento de bibliotecas de classes (frameworks) para análise de sistemas através do método de Elementos Finitos - Rogerio Lopes Braga (2000)
This work shows an object oriented system development. This system implements the Finite Elements Method to calculate electromagnetics features on a defined surface. The Finite Elements method has a very important feature: this method always performs the same basic steps to solve all kinds of problems. This feature, added to the technology that has been used, gives the system the possibility to become a framework. That is this the work goal: the development of a framework for the finite elements method. Following the general bases to build a framework, we have studied some existent application and extract the basic structure of the system from them. Various object oriented techniques were used to implement the framework: the inheritance, the polymorphism and the functions dispatch. Classes of easily understanding and manipulation were developed, generating a very general implementation. The development cicle was splited into parts, with part consisting of a new application prototype, adding more information to the existent structure. During the development, of those parts, the advantages of frameworks clearly appeared: easily implementation of new features and a variety of tests, because the same basic structure is always executed to all kinds of problems. The final product is very well documented, is easily to be understanding, because of generality, and with all the other features gotten by the frameworks.